Ionizing radiation alters organoid forming potential and replenishment rate in a dose/dose-rate dependent manner. (31st December 2021) - Fujimichi, Yuki; Otsuka, Kensuke; Tomita, Masanori; Iwasaki, Toshiyasu
Abstract: Intestinal organoids are an in vitro cultured tissue model generated from intestinal stem cells, and they contain a mixture of epithelial cell types. We previously established an efficient 'one cell/well' sorting method, and defined organoid-forming potential (OFP) as a useful index to evaluate the stemness of individual cells. In this study, we assessed the response to radiation dose and dose-rate by measuring both OFP and the percentage of stem cells in the crypts. After high-dose-rate (HDR, 0.5 Gy/min) irradiation in vivo, the percentage of stem cells in the harvested crypt cells decreased, and the replenishment of cycling stem cells originating from dormant cells was enhanced, but OFP increased in cells irradiated with a total dose of >1 Gy. In contrast, at a total dose of 0.1 Gy the percentage of stem cells reduced slightly, but neither replenishment rate nor OFP changed. Furthermore, the response to 1 Gy of low-dose-rate (LDR) irradiation was similar to the response to 0.1 Gy HDR irradiation. These results suggest that 0.1 Gy HDR irradiation or 1 Gy LDR irradiation does not alter stemness. Additionally, the OFP increase in the colon in response to irradiation was smaller than that in the duodenum, similar to the percentage of stem cells. Understanding the differences in the response of stem cells between the colon and the duodenum to radiation is important to clarify the mechanisms underlying the development of radiation-associated intestinal cancers.